2006
DOI: 10.1107/s0907444906014855
|View full text |Cite
|
Sign up to set email alerts
|

Suggestive evidence for the involvement of the second calcium and surface loop in interfacial binding: monoclinic and trigonal crystal structures of a quadruple mutant of phospholipase A2

Abstract: The crystal structures of the monoclinic and trigonal forms of the quadruple mutant K53,56,120,121M of recombinant bovine pancreatic phospholipase A2 (PLA2) have been solved and refined at 1.9 and 1.1 A resolution, respectively. Interestingly, the monoclinic form reveals the presence of the second calcium ion. Furthermore, the surface-loop residues are ordered and the conformation of residues 62-66 is similar to that observed in other structures containing the second calcium ion. On the other hand, in the trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…We present a case study (Fig. 1) where we have used the parameter DPI to select a representative structure from a set of ten bovine pancreatic phospholipase A 2 structures (Kanaujia & Sekar, 2008;Rajakannan et al, 2002;Sekar et al, 2006Sekar et al, , 1999Yu et al, 2000;Huang et al, 1996;Kumar et al, 1994). The resolution of all ten structures is 1.9 Å .…”
Section: Case Studies 41 Selecting a Structure From A Set Of Homolomentioning
confidence: 99%
“…We present a case study (Fig. 1) where we have used the parameter DPI to select a representative structure from a set of ten bovine pancreatic phospholipase A 2 structures (Kanaujia & Sekar, 2008;Rajakannan et al, 2002;Sekar et al, 2006Sekar et al, , 1999Yu et al, 2000;Huang et al, 1996;Kumar et al, 1994). The resolution of all ten structures is 1.9 Å .…”
Section: Case Studies 41 Selecting a Structure From A Set Of Homolomentioning
confidence: 99%
“…The Second Calcium Compensates for the Effect of High pH on K 2 # . PLA2 binds the second calcium via a low-affinity site that includes E71, and possibly D66 and E92 (37). This influences the PLA2 binding to the zwitterionic interface with a K Ca 2 of 5 mM at pH 8 and 2 mM at pH 6.5 (13).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, IW10 (a buried water molecule) stabilizes the loop residue Ser85 and the N-terminal capping residue Asn88 of the 5 helix. Furthermore, the second calcium-coordinating residues Asn71 and Glu92 have been suggested to be responsible for the binding of the enzyme to the membrane (Sekar, Yogavel et al, 2006). It has also been observed that water molecules IW20 and IW6 are mediated through another invariant water molecule IW18, which is further hydrogen bonded to Asn97.…”
Section: Figurementioning
confidence: 99%
“…(2001); 2 and 4,Sekar et al (2005); 3 and 12,Sekar, Yogavel et al (2006) 5, Sekar et al (2004; 6, 8 and 9,Kanaujia & Sekar (2008); 7,; 10,Rajakannan et al (2002); 11,Sekar, Gayathri et al (2006); 13,Dijkstra et al (1981); 14,Yu et al (2000); 15,Sekar, Sekharudu et al (1998); 16, 24 and 25, Sekar et al (1999); 17,Sekar, Kumar et al (1998); 18, Sekar, Eswaramoorthy et al (1997); 19, Sekar et al (2003); 20,Kumar et al (1994); 21,Huang et al (1996); 22 and 23,Sekar, Yu et al (1997). ‡ ANN, 4-methoxybenzoic acid; TSA, 1-O-octyl-2-heptylphosphonyl-sn-glycero-3-phosphoethanolamine;…”
mentioning
confidence: 99%